Congenital Malformations in the Moroccan Surveillance System: Contribution to Prevalence Estimation - Soukaina Kannane; Samia Boussaa; Jamila El Mendili; Oulaid Touloun (Hindawi - Cambridge University Press, 2024)
Background. Congenital malformations (CMs) are a group of structural or functional anomalies present at birth. These anomalies result in a high rate of mortality, morbidity, and disability in children. CMs are a major public health problem and place a heavy burden on healthcare systems in both developed and developing countries including Morocco, which has had a CMs surveillance system in place since 2011. The aim of this study is to determine the prevalence of CMs in Morocco. Methods. In this study, the epidemiology of CMs in Morocco was assessed retrospectively using the national surveillance system data gathered from case notification forms from 2017 to 2021. Results. The main results showed that the prevalence of CMs in Morocco is 3.91/1000 live births (LBs), and the minimum annual prevalence of CMs was reached in 2017 (3.10/1000 LBs) while the maximum annual prevalence was recorded in 2018 (4.55/1000 LBs). The majority of CMs are unspecified CMs (68.55%), neural tube defects (NTDs) account for (21.13%), and orofacial clefts (OFCs) account for (10.32%). In addition, the majority of CMs (61.73%) were from rural areas. According to region, the Dakhla-Oued Eddahab region recorded the highest prevalence of CMs in Morocco, with 8.81/1000 LBs, while the lowest prevalence was recorded in the Rabat-Sale-Kenitra region, with 2.02/1000 LB. Conclusions. This study reveals that the national prevalence of CMs is high and may be underestimated, as most of the CMS reported is unspecified. The use of a CM registry with detailed reporting of all CMs and the promotion of preventive measures are urgently recommended.